Maternal Mortality Risk Factors in Dr. Hasan Sadikin General Hospital, Bandung in 2009−2013 - Shely Karma Astuti; Muhammad Alamsyah Aziz; Insi Farisa Desy Arya (Faculty of Medicine Universitas Padjadjaran, 2017)
Objective: To discover the factors affecting the occurrence of maternal deaths. The high maternal mortality rate (MMR) in Indonesia is still a common problem which needs urgent solution.Methods: This is an analytic observational, cross-sectional study using a case control approach Fifty two cases were selected as cases, another 52 were selected as control. The sampling was performed by simple random sampling. The instruments used in this study were the medical records of mothers who gave birth in Dr. Hasan Sadikin General Hospital Bandung from 1 January 2009–31 December 2013. Data analysis was performed using chi-square test. Results: In this study, the results showed that the risk factors contributing to maternal deaths were pregnancy complication (p<0.001), delivery complication (p<0.001), puerpural complication (p=0.022), age (p=0.030), parity (p=0.427), prior medical history (p<0.001), antenatal care (p=0.007), maternal education (p=0.527), and area of residence (p=0.049).Conclusions: The risk factors that contribute to maternal deaths include pregnancy complication, delivery complication, puerpural complication, maternal age, prior medical history, antenatal care, and area of residence. Keywords: Complication, maternal deaths, risk factors DOI: 10.15850/ijihs.v5n2.992